Variable ferry routing algorithm for sparse wireless sensor networks. (2016) - Ning, Tong; Xue, Zhang; ChunShuang, Wang; Jiexu, Hun
In this paper, a ferry-based sparse wireless sensor network is considered, in which information is transferred between ferries and sensors. And a triangulation algorithm and triangular mesh colouring strategy for constructing a ferry route are presented. A moving ferry, while moving along the predetermined route, can cover the entire network, and the related theorems are presented. We propose a variable ferry routing scheme (VFR) in order to reduce the energy consumption of ferries. Through theoretical analysis, the relationship is discussed between key parameters of the system, including message generation interval, message delivery probability and the number of ferries. During the routing process, the number of active ferries is adjusted. Compared to other existing routing algorithms, the simulation results of our scheme demonstrate that VFR minimises the message delivery delay and the overhead radio. Moreover, VFR reduces the energy consumption of ferries.